Technology diffusion in the antipsychotic market: a comparison of France and the USA between 1998 and 2008 - Gallini, Adeline (2013)
OBJECTIVE: Second generation antipsychotics captured the majority of the US antipsychotic market shortly after their introduction. Little is known about how second generation antipsychotics diffused in other countries with different health systems. The objective was to describe trends in antipsychotic use in the US and France from 1998 to 2008. METHODS: After presenting a brief background section on pharmaceutical policies in France and the US, descriptive data on quarterly prescriptions dispensed between 01/1998–09/2008 for oral antipsychotics from Xponent™ for the US, and sales recorded in the GERS database for France are presented. Trends in the share of antipsychotic use for first vs. second generation antipsychotics, and in ingredient-level of second generation antipsychotics use are reported. RESULTS: In the US, between 1998 and 2008, total antipsychotic use increased by 78%. Total use was consistently higher in France despite a 9% decrease during the period. By 2008, second generation antipsychotics represented 90% of the antipsychotic US market vs. only 40% in France. However, average annual growth rates in second generation antipsychotics use were similar in the two countries. In France, there was a steady increase in use of all but one second generation antipsychotic; whereas trends in the use of newer drugs varied substantially by drug in the US (e.g. use of olanzapine decreased after 2003 whereas use of quetiapine increased). CONCLUSIONS: These results highlight markedly divergent trends in the diffusion of new antipsychotics in France and the US. Some of these differences may be explained by differences in health systems, while others may reflect physicians’ preferences and norms of practice.